ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU PENGGUNAAN JAMBAN DALAM MENJAGA KELESTARIAN DANAU SIPIN KOTA JAMBI - Jessy Novita Sari (Poltekkes Kemenkes Jambi, 2016)
People's behavior in conducting activities for daily needs such as bathing, washing anddefecating influenced by the environment. Neighborhoods around water sources such as Lake Sipinutilizing the lake for the purpose of removing impurities (latrines). This research aims to determine thefactors related behavior in latrines usage that do not meet health requirements at Lake Sipin and establisha healthy latrine management strategies for the community. This research used analytic survey, usingcross-sectional design of the study design. The research location in the Kelurahan Legok KecamatanDanau Sipin. Total sample were 100 samples from 998 families residing in the Lake Sipin side as thepopulation. The survey results revealed that there was a significant relationship (p value < 0,05) betweenknowledge, education, attitude, level of income and the home position on the behavior of latrine use onLake Sipin. Advice can be given is expected that the role of government and the private sector inmanaging and coaching in order to change people's behavior and the provision of communal latrines forthe community and make the development of Lake Sipin as ecotourism.